2011
DOI: 10.5455/msm.2011.23.64-68
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Therapy in Adult Patients with Post-corrosive Injuries of Gastrointestinal Tract

Abstract: Introduction. Acute poisonings with corrosive substances may cause serious chemical injuries of the upper gastrointestinal tract, from the mouth to the intestines. They appear as a result of accidental or intentional ingestion of caustic substances and may be found in patients of different ages. The aim of this paper was to present our experience with nutritional support in patients with acute caustic poisonings that hinder normal nutrition. Material and Methods. This retrospective study included 33 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Same procedure is performed in these patients as in patients with Stage I, including consultation with psychiatrist. Nutrition can be liberalized thereafter ( 18 ).…”
Section: Aim Of the Studymentioning
confidence: 99%
“…Same procedure is performed in these patients as in patients with Stage I, including consultation with psychiatrist. Nutrition can be liberalized thereafter ( 18 ).…”
Section: Aim Of the Studymentioning
confidence: 99%
“…After latent period of 4-6 weeks, patient presents again with complaints of persistent vomiting, early satiety and postprandial fullness. 4,5 In our patient we found vomit mixed food at the first time hospitalized and resolve with symptomatic therapy.…”
Section: Discussionmentioning
confidence: 53%
“…Esophageal rest may last until the 10 th day after corrosive ingestion or some authors say until the 15 th day, that is until the first endoscopic control. 5,16 In our case, the child came in late sequele and he ate regular meal but vomit soon after eat. We suggested to ate a liquid meal with small volume and frequent times.…”
Section: Discussionmentioning
confidence: 60%
“…Chibishev et al . suggested that ingested caustic substances with pH values lower than 2 or higher than 12 may be associated with a higher endoscopic injury grade 9 . This finding suggests that the degree of damage detected by endoscopy may be milder in cases where the pH of the caustic substance is in the range of 2–12.…”
Section: Discussionmentioning
confidence: 97%